Development of a Recombinant S1 Domain of the Porcine Epidemic Diarrhea Virus Spike Protein Based ELISA for Virus Detection - Noi, Nguyen Van; Chung, Yao-Chi; Cheng, Ta-Chih (Asian Journal of Biological and Life Sciences, 2016)
A recombinant S1 domain of the porcine epidemic diarrhea virus spike protein (S1), protein-based ELISA was developed to detect porcine epidemic diarrhea virus (PEDV). The S1 gene of PEDV was expressed in Escherichia coli. The puriﬁed recombinant S1 protein was used to immunize rabbits to generate a polyclonal antibody. Immunoﬂuorescence analysis indicated that the anti-PEDV-S1 antibody reacted with PEDV-infected cells. The antibody was utilized to develop an indirect ELISA to detect PEDV. Other viruses, porcine transmissible gastroenteritis coronavirus, avian infectious bronchitis coronavirus, porcine reproductive and respiratory syndrome virus, classic swine fever virus and porcine pseudorabies virus, were unreactive.
Keywords: Coronavirus; PEDV-S1 protein; Porcine epidemic diarrhea virus